Core tungsten transport in WEST long pulse L-mode plasmas. (14th July 2020) - Yang, X.; Manas, P.; Bourdelle, C.; Artaud, J. F.; Sabot, R.; Camenen, Y.; Citrin, J.; Clairet, F.; Desgranges, C.; Devynck, P.; Dittmar, T.; Ekedahl, A.; et al.
Abstract: Tungsten transport is investigated in WEST long pulse L-mode plasmas operated with the strike point on the actively cooled upper tungsten divertor. The pulses are mostly heated by lower hybrid waves. It is experimentally found that tungsten does not centrally accumulate throughout these ∼ 30 s reproducible discharges despite large normalised electron density gradients R / L n e . To explain these observations, turbulent and neoclassical transport of electrons and tungsten ions are computed with GKW Peeters A.G. et al (2009 Computer Phys. Commnun. 180 2650) and NEO Belli E. and Candy J. (2008 Plasma Phys. Control. Fusion 50 095010), Belli E. and Candy J. (2012 Plasma Phys. Control. Fusion 54 015015) respectively. Additionally, interpretative integrated modelling simulations are also performed to keep data coherency despite the lack of measurements of some quantities such as the T i profiles. Modelled R / L n e are found consistent with interferometry inversions and the tungsten peaking factor R / L n W remains comparable to R / L n e due to dominant turbulent diffusivities inside r / a = 0.3 − 0.8 . In the central region r / a < 0.3 neoclassical W transport dominates but the convective velocities are several order of magnitudes lower compared to plasmas with toroidal rotation velocities induced by a neutral beam injection (NBI) torque. Finally, nitrogen is seeded in these pulses leading to an enhanced energy content which is consistent with stabilised ion temperature gradient modes from dilution.